Oxytocin enhances social recognition by modulating cortical control of early olfactory processing - Oettl, Lars-Lennart; Schneider, Miriam; Meyer-Lindenberg, Andreas; Grinevich, Valéry; Kelsch, Wolfgang (Neuron, 2016)
Oxytocin promotes social interactions and recognition of conspecifics that rely on olfaction in most species. The circuit mechanisms through which oxytocin modifies olfactory processing are incompletely understood. Here, we observed that optogenetically induced oxytocin release enhanced olfactory exploration and same-sex recognition of adult rats. Consistent with oxytocin’s function in the anterior olfactory cortex, particularly in social cue processing, region-selective receptor deletion impaired social recognition but left odor discrimination and recognition intact outside a social context. Oxytocin transiently increased the drive of the anterior olfactory cortex projecting to olfactory bulb interneurons. Cortical top-down recruitment of interneurons dynamically enhanced the inhibitory input to olfactory bulb projection neurons and increased the signal-to-noise of their output. In summary, oxytocin generates states for optimized information extraction in an early cortical top-down network that is required for social interactions with potential implications for sensory processing deficits in autism spectrum disorders.
Gesehen am 09.05.2019